Decentralised hepatitis C testing and treatment in rural Cambodia: evaluation of a simplified service model integrated in an existing public health system. (May 2021) - Zhang, Meiwen; O'Keefe, Daniel; Craig, Jennifer; Samley, Keo; Bunreth, Voeurng; Jolivet, Pascal; Balkan, Suna; Marquardt, Tonia; Dousset, Jean-Philippe; Le Paih, Mickael
Summary: Background: Direct-acting antiviral treatment for hepatitis C virus (HCV) has provided the opportunity for simplified models of care delivered in decentralised settings by non-specialist clinical personnel. However, in low-income and middle-income countries, increasing overall access to HCV care remains an ongoing issue, particularly for populations outside of urban centres. We therefore aimed to implement a simplified model of HCV care via decentralised health services within a rural health operational district in Battambang province, Cambodia. Methods: The study cohort included adult residents (≥18 years) of the health operational district of Moung Russei who were voluntarily screened at 13 local health centres. Serology testing was done by a rapid diagnostic test using SD Bioline HCV (SD Bioline HCV, Standard Diagnostics, South Korea) with capillary blood. HCV viral load testing was done by GeneXpert (Cepheid, Sunnyvale, CA, USA). Viraemic patients (HCV viral load ≥10 IU/mL) received pretreatment assessment by a general physician and minimal treatment evaluation tests at the health operational district referral hospital. Viraemic patients who did not have additional complications received all HCV care follow-up at the local health centres, provided by nursing staff, and patients who had decompensated cirrhosis, previously treated with a direct-acting antiviral, HBV co-infection, or other comorbidities requiring observation continued receiving care at the referral hospital with a general physician. Patients deemed eligible for treatment were prescribed oral sofosbuvir (400 mg) and daclatasvir (60 mg) once a day for 12 weeks, or 24 weeks for patients with decompensated cirrhosis or those previously treated with a direct-acting antiviral. HCV cure was defined as sustained virological response at 12 weeks after treatment (HCV viral load <10 IU/mL). Patients were assessed for serious and non-serious adverse events at any time between treatment initiation and 12 weeks post-treatment testing. Findings: Between March 12, 2018, and Jan 18, 2019, 10 425 residents (ie, 7·6% of the estimated 136 571 adults in the health operational district of Moung Russei) were screened. Of those patients screened, the median age was 44 years (IQR 31–55) and 778 (7·5%) were HCV-antibody positive. 761 (97·8%) of 778 antibody-positive patients received HCV viral load testing, and 540 (71·0%) of those tested were HCV viraemic. Among these 540 patients, linkage to treatment and follow-up care was high, with 533 (98·7%) attending a baseline consultation at the HCV clinic, of whom 530 (99·4%) initiated treatment. 485 (91·5%) of 530 patients who initiated treatment received follow-up at a health centre and 45 (8·5%) were followed up at the referral hospital. Of the 530 patients who initiated direct-acting antiviral therapy, 515 (97·2%) completed treatment. Subsequently, 466 (90·5%) of 515 patients completed follow-up, and 459 (98·5%) of 466 achieved a sustained virological response at 12 weeks after treatment. Two (0·4%) adverse events (fatigue [n=1] and stomach upset [n=1]) and five (0·9%) serious adverse events (infection [n=2], cardiovascular disease [n=1], and panic attack [n=1], with data missing for one of the causes of serious adverse events) were reported among patients who initiated treatment. All serious adverse events were deemed to be unrelated to therapy. Interpretation: This pilot project showed that a highly simplified, decentralised model of HCV care can be integrated within a rural public health system in a low-income or middle-income country, while maintaining high patient retention, treatment efficacy, and safety. The project delivered care via accessible, decentralised primary health centres, using non-specialist clinical staff, thereby enhancing the efficient use of limited resources and maximising the potential to test and treat individuals living with HCV infection. Funding: Médecins Sans Frontières.